2017
DOI: 10.1021/acs.energyfuels.7b02555
|View full text |Cite
|
Sign up to set email alerts
|

Selective Isomerization of n-Butane over Mordenite Nanoparticles Fabricated by a Sequential Ball Milling–Recrystallization–Dealumination Route

Abstract: For the first time, a sequential fabrication step involving mechanochemistry, recrystallization, and dealumination was developed to convert low-cost natural zeolites to mordenite (MOR) nanoparticles. Natural zeolites are mostly found having poor textural properties and a high aluminum content, which are not suitable for most industrial catalytic reactions. The parent natural zeolites within the size of 1−10 μm were treated by ball milling to obtain nanosized particles with size in the range of 20− 160 nm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This enhanced the access of n -butane into the high strong acid sites in the side pocket of 8-MR channels. This finding was in agreement with literature reports that the acid treatment created the access to the new micropore channels in the side pocket. , Niwa et al studied the acid sites in the 8-MR and found they were stronger than those in the 12-MR. Hence, the high selectivity to isobutane over the H-P-H is most likely contributed through the monomolecular pathway on the strong acid sites.…”
Section: Resultssupporting
confidence: 92%
“…This enhanced the access of n -butane into the high strong acid sites in the side pocket of 8-MR channels. This finding was in agreement with literature reports that the acid treatment created the access to the new micropore channels in the side pocket. , Niwa et al studied the acid sites in the 8-MR and found they were stronger than those in the 12-MR. Hence, the high selectivity to isobutane over the H-P-H is most likely contributed through the monomolecular pathway on the strong acid sites.…”
Section: Resultssupporting
confidence: 92%
“…The important factors influencing the product distribution on the MTH process were process reaction conditions (temperature, WHSV, and pressure), , acidity of the catalyst, , and morphology and structure of the ZS-5 catalyst. ,,, In this experiment, the effect of the temperature, calcium metal impregnation over the ZS-5 catalyst, and WHSV was evaluated on the product distribution for the MTH reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that a modified ZSM-22 catalyst with iron could enhance the catalyst lifetime and selectivity for 3 h and 54%, respectively. In addition, Kurniawan et al 12 studied the modified natural zeolite for increasing the isobutene selectivity from n-butane. They found that ball milling of natural mordenite followed by hydrothermal recrystallization could recover the crystallinity of natural zeolite nanoparticles and, as a result, increase the isobutene selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…From this point, the zeolite catalysts are thermodynamically less favorable in n ‐alkane isomerization despite that there are many attempts made on them. The zeolite catalysts must be operated at a higher temperature, typically 200°C to 300°C because of their weaker acidity compared with the Cl‐Al 2 O 3 and SZ catalysts . In conclusion, the SZ‐based catalysts not only have a satisfied catalytic performance in n ‐alkane isomerization compared with the Pt/Cl‐Al 2 O 3 catalysts but also have no problem with the loss of active components.…”
Section: Why Sulfated Zirconia?mentioning
confidence: 99%